2021
DOI: 10.1111/odi.13830
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐873‐5p modulates progression of tongue squamous cell carcinoma via targeting SEC11A

Abstract: Objective To explore the effect of miR‐873‐5p on proliferation, apoptosis, migration, and invasion of tongue squamous cell carcinoma (TSCC) by targeting SEC11A. Methods Tongue squamous cell carcinoma tissues were collected and performed by qRT‐PCR and Western blotting to determine the expression of miR‐873‐5p and SPC18. SCC9 and CAL‐27 cells were transfected and divided into Mock, mimic NC, miR‐873‐5p mimic, SEC11A, and miR‐873‐5p mimic + SEC11A groups. Then, a series of experiments including cell count kit 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…SEC11A can promote the phosphorylation of EGFR and the downstream kinases, including ERK and Akt (3). This association was confirmed in tongue squamous cell carcinoma, a major subtype of head and neck squamous cell carcinoma [ 6 ]. EGFR is overexpressed in approximately 50 to 90% of head and neck squamous cell carcinoma cases [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…SEC11A can promote the phosphorylation of EGFR and the downstream kinases, including ERK and Akt (3). This association was confirmed in tongue squamous cell carcinoma, a major subtype of head and neck squamous cell carcinoma [ 6 ]. EGFR is overexpressed in approximately 50 to 90% of head and neck squamous cell carcinoma cases [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 89%
“…Its expression serves as an independent prognostic biomarker for patients with CRC [ 3 ], basal-Like bladder cancer [ 4 ] and esophageal squamous cell carcinoma [ 5 ]. One recent study found that inhibiting SEC11A can reduce proliferation, migration, and invasion and induce apoptosis of tongue squamous cell carcinoma [ 6 ], suggesting a potential oncogenic role of this gene in head and neck squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, miR-873-5p is up-regulated in 4 types of cancers, including NSCLC ( 4 ), lung adenocarcinoma (LUAD) ( 28 , 29 ), lung cancer (LCA) ( 5 , 8 , 30 ), and Merkel cell carcinoma (MCC) (24627810). miR-873-5p is down-regulated in 14 types of cancers, including nasopharyngeal carcinoma (NPC) ( 32 ), lung cancer (LCA) ( 33 ), cervical cancer (CC) ( 34 , 35 ), EC ( 36 ), BC ( 10 , 11 , 37 , 38 ), pancreatic ductal adenocarcinoma (PDAC) ( 39 ), glioblastoma (GM) ( 9 , 40 42 ), osteosarcoma (OS) ( 43 ), papillary thyroid carcinoma(PTC) ( 44 ), CRC ( 6 , 45 49 ), esophageal cancer(ESCA) ( 50 ),GC ( 7 , 51 , 52 ), tongue squamous cell carcinoma (TSCC) ( 53 ), and pancreatic cancer(PC) ( 54 ).…”
Section: Mir-873-5p Dysregulation In Various Cancersmentioning
confidence: 99%
“…Forced expression of SEC11A may activate gastric cancer progression via promoting TGF-α secretion. Interestingly, study found that high SEC11A expression was examined in squamous cell carcinoma of tongue and its activation induced proliferation, migration, and invasion in tongue squamous cell carcinoma cells [7]. SEC11A up-regulation is in relation to increased cancer-specific mortality among esophageal squamous cell carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%